The Effectiveness of an Anti-Bullying Program on Academic Hope in Elementary School Students - Badri, Rahman; Mehr, Akram Aria (Journal of Social and Scientific Education, 2025)
Bullying in schools has negative consequences on students' mental health and academic performance. This study aimed to examine the effectiveness of the anti-bullying program on the academic hope of elementary school students. The study employed a quasi-experimental pretest-posttest design with a control group. This design was chosen due to ethical and practical constraints in randomizing schools. The statistical population included all sixth-grade students in Ahar city (N=3,829) in 2025. A sample of 40 students was selected through cluster random sampling and assigned to experimental and control groups (20 students each). The experimental group participated in the anti-bullying program for 15 sessions (45 minutes each). Data were collected using the Academic Hope Scale, which demonstrated good reliability (α=0.87 for the full scale, α=0.82 for the "pathway" component, and α=0.79 for the "agency" component). Due to the presence of multiple dependent variables and the need to control for pretest effects, multivariate analysis of covariance (MANCOVA) was conducted using SPSS-26. The results showed that the Olweus bullying prevention program significantly improved academic hope in the experimental group (an increase of 8.6 points, p<0.01). Statistical analyses confirmed strong effects for the pathway component (F(1,37)=5.43, p=0.027, η²=0.162) and the agency component (F(1,37)=10.001, p=0.004, η²=0.263), indicating a significant improvement in academic hope. Based on the findings, the anti-bullying program can significantly enhance academic hope by strengthening students' beliefs in their individual abilities and creating a safe environment. It is recommended that this program be included as a key strategy in the educational policies of the Ministry of Education.